Lagoinha region: Transiting between Subjectivities - Faria Starling Solla, Lawrence; Luiza Castro, Maria (Seven Editora, 2023)
If, in the past, from an inflection at the moment when the modern era was inaugurated, society has experienced a considerable change in its power relations, these relationships are currently going through a new moment of change. At the beginning of the Modern era, according to Michel Foucault, there was the transition from a society based on the dominant-dominated dichotomy to a discipline-based society. At the present time, there is the transition of this society from discipline to the control society, based on continuous control and instant communication. The society of discipline sought to shape the bodies to certain models and truths and Gilles Deleuze argues that the disciplinary crisis began after the Second World War. In the control society, the molds become quickly and continuously, which prevents the identification of the models, causing it to operate more and more by the production of subjectivities. Sophisticated mechanisms of "truth creation" and "consensus building" are developed. Taste and opinions are manipulated through the construction and instant dissemination of systems of signs and images: it is the era of spectacle, the production of ephemeral images for the general public, through the creation of stable images, surrounded by authority and power. In the case of the Bonfim and Lagoinha neighborhoods in Belo Horizonte, the images and signs, now simply appropriate, or intentionally forged the s, can be lido s as one of these mechanisms of formation of subjectivities at the service of the ruling classes. At the first moment in history, the neighborhoods were the place of the working class, outsiders and immigrants, prostitutes, outcasts, cemetery and the supernatural. In a second moment, however, it becomes a violent and dangerous place, although culturally rich; degraded, though well located; which houses small "cracolândias" and, therefore, a place that "deserves" and "should" be revitalized. This article intends to analyze, in the light of the actor-network theory (ANT), according to Bruno Latour's perspective, the dynamics that occur in the territory, from the interaction between the actors involved, whether human or non-human, mapping the characteristics, interests, the way they relate to each other and to the territory. As the author points out, through the narratives elaborated by the actors, it is possible to identify the controversies. And it is precisely through these controversies that new – sometimes unpublished – views are instituted, enabling new readings of social dynamics in the face of the imminent – if not already existing – process of gentrification in this territory. DOI: https://doi.org/10.56238/tfisdwv1-141